Nurse–physician collaboration, autonomy, and decision-making ability among intensive care unit nurses in Tehran, Iran: A cross-sectional study - Sogand Sarmadi; Neda Sanaie; Mahsa Boozari Pour; Akbar Zare-Kaseb (PLoS ONE, 2025)
Background Clinical decision-making by intensive care unit nurses is vital for ensuring patient safety. It is hypothesized that professional autonomy and interprofessional collaboration are determinants that influence the quality of decision-making; however, empirical evidence supporting this hypothesis within Iranian intensive care unit settings remains limited. Objective To examine the correlations between perceived autonomy, nurse–physician collaboration, and clinical decision-making ability among intensive care unit nurses. Methods This study employed a cross-sectional design, with 400 intensive care unit nurses from two university hospitals in Tehran completing validated Persian versions of the P-AITCS-II, the Dempster/DPBS, and the Lauri & Salanterä instruments to measure interprofessional collaboration, professional autonomy, and clinical decision-making, respectively. We followed STROBE reporting recommendations. Descriptive statistics characterized the sample and scale scores. Bivariate associations were assessed using correlation and group-comparison tests, and multiple linear regression was employed to estimate the independent associations of autonomy and collaboration with decision-making after adjusting for relevant covariates. Ethical approval and informed consent were obtained. Results The study sample comprised 400 participants, with a mean age of 33.19 years (SD = 5.67). In bivariate analyses, higher perceived autonomy and greater interprofessional collaboration were positively associated with better clinical decision-making (p < 0.05). In multivariable linear regression models that included covariates, perceived autonomy and interprofessional collaboration remained independent predictors of decision-making ability (p < 0.05). The entire model explained approximately 14.2% of the variance in decision-making, suggesting that additional determinants may influence nurses’ decision-making processes. The total mean score of the participants was classified at an intuitive–analytic decision-making level, indicating a combined reliance on experience-based intuition and structured analytic processes. Conclusions Among the intensive care unit nurses within this sample, higher perceived professional autonomy and enhanced interprofessional collaboration were independently correlated with improved self-reported clinical decision-making capabilities. Given the cross-sectional nature of the study, causality cannot be established. Longitudinal research employing objective performance metrics is necessary to examine causal relationships and to guide organizational strategies that foster both autonomy and collaborative practice.